Natural Resources Management Constraints in Farming in Eastern Uttar Pradesh -a Case Study - Mishra, A.K.; Bihari, B.; Chauhan, S.K.S. (Journal of Soil and Water Conservation, 2022)
Participatory Rural Appraisal (PRA) techniques were adopted to identify the natural resources management related constraints in farming in the Pithla village in Amaniganj Block of Faizabad District in eastern Uttar Pradesh. The study identified acute shortage of water for irrigation at the time of need as the most serious problem adversely affecting the agricultural production and productivity. Rapid expansion of salt affected soils (Usars) to the fertile tracts, degradation of productive farm lands and rapid depletion of ground water resources were some of the main natural resources constraints faced by the farmers. Due to poor institution-village linkages, the relevant research findings are not getting adopted in the field. There is an urgent need for active participation of government and non-government agencies in narrowing the gap between research and development. This would solve the problems of natural resource management and ensure enhanced agricultural production for the improvement of the socio-economic conditions of peasants of eastern Uttar Pradesh.